Design and simulation of microactuator for magnetic recording head - Kajohn Choobthaisong; Afzulpurkar, Nitin V.; Adisorn Tuantranont; Lertsak Lekawat; RTG Fellowship; National Electronics and Computer Technology Center (NECTEC); National Science and Technology Development Agency (NSTDA) (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
This thesis discusses the design and simulation of MEMS microactuator for a dual-stage servo system in hard disk drive. The microactuator utilizes parallel-plates actuation and position sensing controller which will be completely batch fabricated at low production cost. The microactuator is mounted between the slider and suspension and drives the slider on which a magnetic head element is attached. The microactuator has an electrical microstructure directly processed from SOl wafer which consist of stator attached to the substrate and a movable rotor connected to the spring beam. In the design, avoidance anchored in the movable stage. The design of electrostatic force actuation generate sufficient out put force to move a conventional slider in hard disk drive. When voltage is applied to the actuator, the microactuator will drive the head to move in tracking direction by the rotational motion of the rotor. The software is used in the simulation is Conventor ware. The microactuator is capable that ± 0.5 11m equivalence displacement of the head element in tracking direction is achieved under the driving voltage 50 V
A thesis submitted in pa11ial fulfillment of the requ irements for the degree of Master of Engineering, School of Engineering and Technology, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2006
Keywords: Microactuators -- Simulation methods; Magnetic recorders and recording -- Heads